2015
DOI: 10.1093/rheumatology/kev097
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension in systemic lupus erythematosus may benefit by addition of immunosuppression to vasodilator therapy: an observational study

Abstract: Immunosuppression and vasodilators produced significant improvement in SLE PAH over 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…Tanaka et al46 reported a significant reduction of RVSP in seven out of eight patients who received corticosteroids ± cyclophosphamide (CYC) – two patients relapsed and were again treated successfully. Intravenous CYC pulses (dose ranging from 500 mg/month to 1,000 mg/m 2 /month) were also administered in five cohort studies in conjunction with prednisone (0.5–1 mg/kg/day with slow tapering)47,48 and vasodilators49,50 or PDE5 inhibitors 51. Gonzalez-Lopez et al47 showed that CYC in combination with low doses of prednisone (<15 mg/day) was effective in 16 patients with moderate SLE-PAH as assessed by TTE.…”
Section: Therapeutic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanaka et al46 reported a significant reduction of RVSP in seven out of eight patients who received corticosteroids ± cyclophosphamide (CYC) – two patients relapsed and were again treated successfully. Intravenous CYC pulses (dose ranging from 500 mg/month to 1,000 mg/m 2 /month) were also administered in five cohort studies in conjunction with prednisone (0.5–1 mg/kg/day with slow tapering)47,48 and vasodilators49,50 or PDE5 inhibitors 51. Gonzalez-Lopez et al47 showed that CYC in combination with low doses of prednisone (<15 mg/day) was effective in 16 patients with moderate SLE-PAH as assessed by TTE.…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…More recent studies demonstrated that the addition of vasodilators and supportive treatment with diuretics and anticoagulants may benefit patients with more severe PAH at diagnosis; in those studies, patients with MCTD were also included 49. Finally, Kommireddy et al51 reported a mean reduction of 16 mmHg in PASP (assessed by TTE) with three intravenous CYC pulses plus oral prednisone and PDE5 inhibitors in 11/24 patients with SLE-PAH. Moreover, rituximab was shown to provide benefit in a refractory case of SLE-PAH,52 while another patient was successfully managed with mycophenolate mofetil and cyclosporine 12.…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…86 Immunosuppressive therapy is routinely administered in patients with connective tissue disease associated with PAH and has been shown, in conjunction with vasodilators, in mostly observational studies to improve functional class and hemodynamics in patients with lupus and mixed connective tissue disease. 87,88 Several inflammatory and immune cell modulators including mycophenolate mofetil, leukotriene inhibitors, and anti-CD20 antibody have been investigated as therapeutics in PAH and demonstrated benefit in animal models. [89][90][91] Further studies and experimental models are needed to determine the benefit of pre-existing or novel therapeutics that target the different cell types involved in this immune/inflammatory disturbance.…”
Section: T-cells (Cd3+) Cytotoxic T-cells (Cd8+) and Helper T-cellsmentioning
confidence: 99%
“…One of the most distinctive aspects of CTD‐PAH from other PAH is response to immunosuppression. Treatment combining glucocorticoids and intravenous cyclophosphamide (IVCY) may result in clinical improvement in patients with SLE‐, MCTD‐ or primary Sjögren's syndrome‐PAH but has failed to show response in those with SSc‐PAH . However, there is currently no answer on a case of overlap syndrome, such as patients who have both SSc and SLE.…”
Section: Role Of Immunosuppressionmentioning
confidence: 99%
“…However, there is currently no answer on a case of overlap syndrome, such as patients who have both SSc and SLE. Addition of immunosuppression to PAH‐specific vasodilator therapy may produce a further therapeutic effect in SLE‐PAH patients . Of note, vasodilator resistant case may also respond to immunosuppression .…”
Section: Role Of Immunosuppressionmentioning
confidence: 99%